Hot rocks - Ryan, Denise (Sydney : Weldon Owen Pty, 2008)
These books are designed for children who recognise familiar words with ease, and are developing a range of word attack skills. There are varied, simple sentence patterns, many familiar objects and actions, and illustrations that provide moderate to high support. Some specialised vocabulary is introduced in this stage. A series of beautifully designed, fact-filled books, richly illustrated with a wealth of accurate, full-colour illustrations, intriguing diagrams, cross sections and cutaways. The text has been carefully leveled to support children's reading development. Ideal to help all beginner readers gain confidence while they practice their reading skills enthusiastically.